Methods and logistics of an oral health cohort of university students from Pelotas, a Brazilian Southern city - Luiz Alexandre Chisini; Mariana Gonzalez Cademartori; Kauê Collares; Sandra Beatriz Chaves Tarquinio; Marília Leão Goettems; Flávio Fernando Demarco; Marcos Britto Corrêa; Marina Souza Azevedo (Universidade Estadual de Campinas, 2019)
Aim: This paper aimed to describe the methodological aspects in the baseline of university students' cohort in a public university in southern Brazil. Methods: A multidisciplinary study was carried out assessing the psychosocial and oral health conditions of university students at the Federal University of Pelotas (UFPel). All new university students who have entered in in UFPel in the first semester of 2016 year were invited to participate. Two self-administered questionnaires were applied in classrooms. Descriptive analysis was performed using Stata 14.0. Results: A total of 3,237 students were eligible. Of these, 2,089 (64.5%) signed the consent form to participate of the study and answered the general questionnaires, and 2,052 (63.4%) students answered the confidential questionnaire. Refuses represented only 1.4% (n=29) of the total sample. Overall, most of the sample was female (52.2%), with age ranging from 18 to 24 years (66.1%), with white skin color (74.1%) and with mothers with educational level at university course (32.4%). A total, 62% reported a family income between 1001.00 and 5000.00 BRL, while only 16.3% reported being from low-income family (≤ 1000.00 BRL).  The UFPel offers 63 classroom-based courses classified in nine areas of knowledge. The Applied Social Sciences area comprised 19% of the sample followed by the Linguistics, Letters and Arts (17%) area and the Health sciences area (13%). Conclusion: To the knowledge of researchers, this was the first cohort study of university students in the South of Brazil including more than two thousand participants. This paper described strategies adopted to optimize and to allow data collection in the baseline and in the next follow-ups.